Adventure activities in nature and development of pro-environmental behavior: Comparative analysis between elderly practitioners and their conductors - Chao, Cheng Hsin Nery; Figueiredo, Juliana de Paula; Dias, Viviane Kawano [UNESP]; da Fonseca, Cinthia Beatriz; Sobrinho, Ivan Igor de Oliveira; Tavares, Giselle Helena; Schwartz, Gisele Maria [UNESP] (Universidade Federal do Rio Grande do Sul, 2015)
This qualitative study aimed at comparing results regarding pro-environmental behavior of elderly practitioners and conductors of adventure activities. The Ecocentrism and Anthropocentrism Scale (THOMPSON; BARTON, 1994) was applied to intentional samples of elderly practitioners and young adult conductors of adventure activities in nature. Data were descriptively analyzed by content analysis and indicate that elderly and younger adults are included in the ecocentric dimension. However, the former are more anthropocentric and environmentally apathetic. New studies are suggested to sub-sidize new action strategies in the Human Motricity field, to stimulate the development of pro-environmental behavior.
Actividades de aventura en la naturaleza y desarrollo comportamiento proambiental: Análisis comparativo entre personas mayores y conductores
Atividades de aventura na natureza e desenvolvimento do comportamento pró-ambiental: Análise comparativa entre idosos e condutores
Keywords: Elderly; Environmental Education; Nature